STATUS HARA N, P, K TANAH DAN REKOMENDASI PEMUPUKAN TANAMAN TEBU (Saccharum officinarum Linn.) DENGAN ANALISIS CLUSTER - , basuki ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Indonesian sugar industry is under mounting pressure to minimise off-farm losses of nutrients and reduce its overall costs of production. Fertilizer inputs absorb production costs 65% of the total cost. One effort that can be done is an application of specific fertilizer recommendations based on soil analysis. This study aims to classify plot status the nitrogen total, posphate available, kalium exchange and Cluster fertilizer recommendation sugarcane (Saccharum officinarum Linn.) in Unit PG. Djatiroto, Lumajang plantation in mapping. Analysis done for 48 grids with each grid to cover 6,25 ha area. The Clustering based on concentration variable of t nitrogen total, posphate available, kalium exchange, with Hierarchical Analysis Cluster and Geographical Information System (GIS) methods, starting from January until May 2014. The analysis result have 5 Cluster fertilizer recommendation. Those are: One Cluster(Cluster 3) which consist of one grid with recommedation of 160 kg /ha, 90 kg P2O5/ha, 145 kg K2O/ha